Dracula - Zamorsky, Tania; Akib, Jamel; Stoker, Bram, 1847-1912. (New York : Sterling Pub., 2007)
A retelling of Bram Stoker's famous novel in which a small group of people discover the double identity of the wealthy Transylvanian nobleman Count Dracula and vow to rid the world of the evil vampire.
5.4
3-6
3-6
Keywords: Vampires -- Juvenile fiction; Dracula, Count (Fictitious character) -- Fiction; Horror stories; Vampires -- Fiction; Dracula, Count (Fictional character) -- Fiction; Horror fiction; Vampires -- Fiction; Horror fiction